Hotel Classification Systems : A Case Study - Sufi, Tahir; Singh, Satinder Pal (Prabandhan: Indian Journal of Management, 2018)
Hotel classification systems are used by almost all the countries to create the hierarchy of hotels based on service quality. This study examined how different systems of hotel classification evaluate hotel properties to allocate ‘star’ or ‘diamond’ ratings. The study, based on Yin’s (1994) approach for case study analysis, used convenience sampling method for the study. Five such systems used in different parts of the world were chosen for the study during January-March 2016. The documents related to the hotel classification systems were downloaded from the official websites of the concerned agencies. Document analysis and content analysis were used to discuss the findings. Apart from pointing similarities and differences, the study indicated that all the hotel classification systems expect four and five-star hotels only to have service quality and hospitality. Important features like sustainability, social media, and innovative methods for evaluating service quality were found to be lacking in all systems. Finally, the study proposed a model for hotel classification.